2010
DOI: 10.1002/anie.201000982
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap‐Like Strong Fluorescence in Functionalized Carbon Nanoparticles

Abstract: Quantum of solace: Fluorescent carbon dots (surface‐passivated carbon nanoparticles) are developed as an alternative to classical semiconductor quantum dots. Gel column chromatography afforded carbon dots with emission yields close to 60 %. Their optical properties resemble band‐gap transitions found in nanoscale semiconductors, thus suggesting that nanoscale carbon particles acquire essentially semiconductorlike characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
401
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 574 publications
(435 citation statements)
references
References 39 publications
27
401
1
4
Order By: Relevance
“…Tian et al [90] firstly reported the utility of 13 CNMR spectroscopy in liquid state to identify the carbon states in a C-dots sample derived from candle shoot (Figure 8). Followed by this, numerous efforts have been contributed to using NMR spectroscopy in both solid state and liquid state for C-dots characterization [21,38,56,85,109,115,135,143,[159][160][161][162][163][164]. In addition, NMR has been proved to be powerful in the establishment of the 8 Journal of Nanomaterials chemical alterations that happened to the surface modifiers during carbonization.…”
Section: Nuclear Magnetic Resonancementioning
confidence: 99%
See 1 more Smart Citation
“…Tian et al [90] firstly reported the utility of 13 CNMR spectroscopy in liquid state to identify the carbon states in a C-dots sample derived from candle shoot (Figure 8). Followed by this, numerous efforts have been contributed to using NMR spectroscopy in both solid state and liquid state for C-dots characterization [21,38,56,85,109,115,135,143,[159][160][161][162][163][164]. In addition, NMR has been proved to be powerful in the establishment of the 8 Journal of Nanomaterials chemical alterations that happened to the surface modifiers during carbonization.…”
Section: Nuclear Magnetic Resonancementioning
confidence: 99%
“…Currently, chromatographic methods available for the separation of Cdots are anion-exchange high performance liquid chromatography (AE-HPLC) [95,100,101,107], reversed-phase-(RP-) HPLC [91,96,108], and size exclusion chromatography (SEC) [97,109].…”
Section: Chromatographic Techniquesmentioning
confidence: 99%
“…The surface of these materials is passivated by chemical functionalization with small chains of polymeric or oligomeric species. 9 Interestingly, excellent biocompatibility and optical properties can be achieved by doping (C)-dots with metals or nonmetals. 10,11 However, despite considerable successes, a challenging problem arises as the metal is often immediately oxidized by atmospheric oxygen on the C-dot surface.…”
Section: Introductionmentioning
confidence: 99%
“…This  PL is relatively high for bare, raw C-dots and C-dot surface functionalisation by covalent attachment of polyethylenglycol units to passivate the surface has been reported to achieve quantum yields of 0.6. 8,43 It could be that  PL of the C-dots when encapsulated inside the rigid zeolite framework is even higher than 0.4, although the lack of transparency of the solid powders makes not possible to quantitatively determine  PL before dissolution of the zeolite and extraction of C-dots-It should also be commented that according to chemical analysis, the C-dots obtained by pyrolysis of the quinolinium ion contains N atoms and that there is one recent precedent reporting that doping with N atoms increases  Pl . 36 It is very likely that also here the high  Pl could be due to doping of the C-dots.…”
Section: Introductionmentioning
confidence: 99%